Faktor Kunci dalam Memilih Perguruan Tinggi di STISPOL Wira Bhakti - Mertaningrum, Ni Luh Putu Erma; Puriati, Ni Made; Merta, I Nengah (Jurnal Ilmiah Global Education, 2025)
Choosing a quality university presents a significant challenge for prospective students in the modern era. With the increasing number of universities, facilities such as classrooms, laboratories, and libraries become major considerations in enrollment decisions. This research examines the role of brand image and brand trust in influencing study decisions at STISPOL Wira Bhakti. Utilizing a quantitative approach and path analysis, this study involves 54 students as respondents. The results indicate that brand image and brand trust have a significant impact on study decisions at STISPOL Wira Bhakti. Additionally, brand trust acts as a strong mediator in this relationship, indicating that a positive university image can enhance prospective student trust. This study offers strategic insights for private higher education institutions, emphasizing the importance of building brand image and brand trust to strengthen attractiveness and credibility in the eyes of prospective students.